How to Interpret Categorical Data in Health Research? - Heru Santoso Wahito Nugroho; Sanglar Polnok; Joel Rey Ugsang Acob; Abdullah Al Mamun; Rafif Naufi Waskitha Hapsari; Rozan Asyrofi Rakyan Risang Aji; Bahtiar Bahtiar; Arief Budiono; Handoyo Handoyo; Hery Koesmantoro; Sunarto Sunarto; Teta Puji Rahayu; Nimsi Melati; Retno Vivi Intening; Suparji Suparji; N. Surtinah; Tri Wahyuni Ismoyowati; Tanko Titus Auta (Alliance oh Health Activists (AloHA), 2025)
In health research, many categorical variables are found that must be analyzed using descriptive statistical methods, then interpreted. Currently, there are still many health researchers who interpret categorical variable data in the health sector in the same way as social research in general, namely focusing on the categories with the largest proportions. In fact, for health research, researchers should focus on the expression of unexpected categories. Therefore, this should be a concern for the health research community, especially in the campus environment as the first place for students and health researchers to study and apply various types of health research. This is an urgency, so that the quality of health research can be immediately improved, especially in terms of data interpretation. It was concluded that there were many errors in interpreting categorical variable data in the health sector, so this had to be anticipated from the time of education on campus. Keywords: health research; categorical variables; data interpretation; unexpected category